Pengaruh Organizational Citizenship Behavior, Motivasi Kerja dan Mutasi Kerja terhadap Komitmen dan Kinerja Pegawai pada Badan Pemeriksa Keuangan Perwakilan Provinsi Jawa Timur di Sidoarjo - Mochammad Balatif; Muslichah Erma Widiana; Yulita Prihati Hartanti (Indonesian Journal of Management Science, 2022)
The purpose of this study is to prove the influence of Organizational Citizenship Behavior, work motivation and work mutations on the commitment and performance of employees at the East Java Provincial Representative Financial Audit Agency in Sidoarjo. The population in this study was 163 auditors. The sampling technique uses the Non Probability Sampling method with the Quota Purposive Sampling approach, so that the respondents used were 112 employees.This study used a data collection method, namely a questionnaire. The data analysis technique used is multiple linier regression analysis. The results of this study explained that Organizational Citizenship Behavior, work motivation and work mutation simultaneously affected employee commitment by 36.4% and employee performance by 25.6%.Initially, all variables have a significant positive effect on employee commitment and employee performance, except that work mutations have not been shown to have an effect on employee commitment. The work motivation factor was able to contribute the most to employee commitment by 30.6%, while work mutation was the dominant factor that was able to contribute to employee performance by 11.2%.